Triple-phase MDCT of liver: Scan protocol modification to obtain optimal vascular and lesional contrast - Sween, Sheoran; Samar, Chatterjee; Binu, Sekhar (Indian Journal of Radiology and Imaging, 2018)
Context: With advances in 16-slice multidetector computed tomography (MDCT), the entire liver can be scanned in 4–6 s and a single breath-hold dual-phase scan can be performed in 12–16 s. Consequently, optimizing the scan window has become critical. Aim: The purpose of our study was to optimize scan delays using bolus-tracking techniques for triple-phase CT of the liver. Settings and Design: Fifty patients with liver lesions were randomly divided into two groups with 25 patients each. The patients were subjected to triple-phase MDCT of liver with two different scan protocols. Materials and Methods: They were administered 1.5 mL/kg of 300 mg/mL of iohexol at a rate of 3.0 mL/s with a pressure injector. Using bolus-tracking program, scans were commenced at 4, 19, and 44 s and 8, 23, and 48 s for the first, second, and third phases, respectively. The mean CT values [Hounsfield unit (HU)] were measured in the aorta, hepatic artery, portal vein, hepatic vein, liver parenchyma, and lesion using circular region of interest cursor ranging in size from 5 to 20 mm in diameter on all phases. Statistical Analysis Used: Statistical analysis was carried out using paired Student's t-test. Results: In hepatic arterial phase, hepatic artery has shown better enhancement in Group B (8 s) (P = 0.0498) compared with Group A (4 s). In portal venous phase, there were no significant differences in contrast enhancement index (CEI) values at any of the six measured regions between the groups. In the hepatic venous phase, liver parenchyma has shown nearly significant (P = 0.0664) higher CEI values in Group B (48 s) when compared with Group A (44 s). Conclusion: A scan delay of 8 s, after trigger threshold (100 HU) is reached in the lower thoracic aorta, is optimal for the early arterial phase imaging, this phase being most helpful for assessment of hepatic arterial tree (CT angiography). The liver parenchyma showed maximum enhancement at 48 s scan delay.
Keywords: Bolus-tracking technique; hepatic angiography; scan delay